Influence Analysis Of Non Performing Financing By Profit-Loss Sharing Financing Contract To The Profitability Of Islamic Commercial Bank In Indonesia - Afkar, Taudlikhul (AKRUAL: JURNAL AKUNTANSI, 2018)
This study discusses to analyze the influence of non performing financing (NPF) from financing for the results seen from Mudaraba and Musharaka contracts to the level of profitability of Islamic banks in Indonesia. The results of this study indicate inconsistency with the theory that profitability is influenced by non performing financing (NPF). This study shows the opposite result of non-performing financing (NPF) as measured from Mudaraba contract and Musharaka contract no significant effect on profitability level of Islamic Banks in Indonesia. Simultaneous tests also show results that have no significant effect. The results of this study indicate that Non Performing Financing does not always have an effect on profitability because the value of financing problem is relatively small.